Efektifitas Pelaksanaan Program Bantuan Stimulan Perumahan Swadaya (BSPS) Di Desa Siwalembu Kecamatan Sojol - Hartin Miftahul Jannah; Erwan Sastrawan; Harnida Wahyuni Adda (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to (1) describe the implementation of the Self-help Housing Stimulant Assistance Program in Siwalempu Village, Donggala Regency. (2) reviewing and measuring the effectiveness of the implementation of the BSPS program in Siwalempu Village, Donggala Regency. (3) future efforts so that program implementation runs effectively. The method used in this research is descriptive method with qualitative research. Sources of research data consist of observations, interviews, results of recording in the field and documentation. Based on the research results, it can be seen that (1) the implementation of the BSPS Program in Siwalempu village has been going quite well. (2) the implementation of the BSPS program in Siwalempu village, Donggala district has not been effective. This can be seen from the implementation of the BSPS program in Siwalempu village, which has not been fully achieved due to the fact that the program has not been fully used referring to the established mechanisms and procedures. This self-help housing stimulant assistance program is able to improve the social life of residents by helping residents in need.